Impact of risk‐stratified mycophenolate dosing in heart transplantation. Issue 11 (6th August 2021) - Alam, Amit; Van Zyl, Johanna S.; Hall, Shelley A.; Sam, Teena
Abstract: Mycophenolate mofetil (MMF), the prodrug of mycophenolic acid, is a highly effective immunosuppressive agent in heart transplant therapy. While the FDA approved dose is 1500 mg twice daily, dosing is often reduced due to dose‐dependent adverse effects. However, empiric MMF dose reductions may lead to sub‐therapeutic dosing and impair clinical outcomes. Our single center protocolized a risk‐stratified approach based on age and weight to dose 500 mg twice daily or 1000 mg twice daily to patients after heart transplantation. This retrospective single‐center study analyzed 140 consecutive heart transplant patients who were initiated on our risk‐stratified MMF protocol post‐transplant. The analysis revealed that the composite rate of biopsy‐proven rejection, graft loss, or mortality at 1‐year post‐transplantation was similar between the two groups. Incidence of neutropenia, thrombocytopenia, infection, cardiac allograft vasculopathy, or acute kidney injury by 1‐year also showed similar results between the two groups. Risk‐stratification of MMF dosing appears to be a safe and effective strategy after heart transplantation.